Pengaruh Good Corporate Governance, Return on Equity, Dan Investment Opportunity Set Terhadap Nilai Perusahaan Pada Perusahaan Subsektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2019 – 2023 - Jihan Nibras Salamah; Esi Fitriani Komara (Faculty of Economics and Business, University of Pancasakti Tegal, 2025)
This study aims to examine how Good Corporate Governance (GCG), Return on Equity (ROE), and Investment Opportunity Set influence the value of companies within the banking sub-sector listed on the Indonesia Stock Exchange (IDX) during 2019–2023. The GCG framework is captured through five main components: managerial ownership, institutional ownership, the proportion of independent commissioners, the board of directors, and the audit committee. Employing a quantitative descriptive method, the research analyzed 20 out of 47 companies, selected using purposive sampling. Data were processed using panel data regression, with the analysis conducted through the Fixed Effect Model, followed by Chow and Hausman tests to identify the most suitable and reliable model for inference. The results indicate that institutional ownership, independent commissioners, audit committees, ROE, and MBVE have a significant impact on firm value, whereas managerial ownership and the board of directors do not exhibit a statistically significant effect, highlighting that some governance aspects may play a more critical role in determining firm valuation than others.